Peranan Penuntut Umum Dalam Menanggapi Indonesia Darurat Narkoba Sebagai Pihak Yang Melakukan Penuntutan Dan Mengajukan Upaya Hukum Demi Mencapai Tujuan Memberantas Narkoba - Nike Dian Pertiwi (Verstek, 2017)
Cases of drug misuse is increasingly making Indonesia in emergencies drugs. Right now we can see now a lot of court decisions that impose criminal sanctions lightly against the criminal misuse of drugs. Suitability of sanctions imposed by the judge on the criminal misuse of drugs is dependent on proving through charges that are charged to the public prosecutor. In addition through the charges the prosecutor is also entitled to file legal action against a court decision which has not fulfilled a sense of justice.      This study aims to determine the role of public prosecutors in Indonesia emergency response study drug through Yogyakarta High Court Decision No. 12 / PID.SUS / 2015 / PT YYK. Results from this study is the author knew the severity of the criminal sanction imposed by the judge depending on the demands formulated by the prosecution. Thus achieved whether or not the objectives of the Act No. 35 of 2009 and for dealing with emergency drug Indonesia, then the integrity of the prosecution should be further improved. This research is a normative law prescriptive approach to legislation, case approach and conceptual approaches. Sources and types of materials used law is the primary legal materials are supported secondary law.     Keywords: the role of the public prosecutor, Indonesia emergency drugs, appeals.